PENINGKATAN PENGETAHUAN MASYARAKAT TERHADAP DRAINASE BERPORUS YANG DIFUNGSIKAN SEBAGAI TEMPAT PERESAPAN AIR HUJAN - Dian Pratiwi; Ria Oktaviani Sinia; Arniza Fitri (Universitas Teknokrat Indonesia, 2020)
The rapid development in Bandar Lampung resulted in the expansion of residential areas and the reduction of green areas as water-retribuid areas. Flash floods have become a common problem in Bandar Lampung during the rainy season since several decade. To reduce the problem of flash floods that are being faced by the people of Bandar Lampung, especially at RT. 005, Jagabaya II Village, Way Halim district, Bandar Lampung city during the rainy season, a PKM team from Universitas Teknokrat Indonesia has socialized about porous drainage. Porous drainage is one of the environmentally friendly drainage methods that is also functioned as a rainwater retention. In addition, the PKM team also trained the people of Jagabaya II Village, Way Halim district in assembling and installing of the porous drainage as an effort to make them as a pilot community that contributes to flood prevention occurred in Bandar Lampung city. Within three days, eight retention points of porous drainage have been installed in flood-prone areas in Jagabaya's II Village. The activities of increasing public knowledge about porous drainage are well done while the people of Jagabaya II Village look enthusiastic and wish more counseling activities to be continued with other topics related to drainage and flood management. Besides, the leader and people of Jagabaya II Village expect ongoing activities such as maximizing the retention points of porous drainage because eight points has not been enough to reduce large volume of flooding in their environment. The community wish that by installing more retention points of porous drainage, it will be able to reduce large volume of flooding that often occurs in their environment, especially during heavy rains. Keywords: Socialization, porous drainage, infiltration rainwater, flood